Attitude regarding Nigerian pidgin english among Nigerian students in Malaysia - Buba, Jamila AbdulAzeez; Al-Shujairi, Yasir Bdaiwi Jasim; Ya'u, Mohammed Sani (Australian International Academic Centre, 2016)
It is quite interesting to note that Pidgin which essentially began as a demanded language between the white importers, who later turned colonial masters, and their black traders has now become a campus language-spoken of the majority of the population among the Nigerian students in advanced institutions of learning. Nigerian Pidgin English evolved as a result of language contact with the British colonialists. This study seeks to assess the use, and also determine the recognition of Pidgin English among Nigerian postgraduate students in Universiti Putra Malaysia. Questionnaires were administered on selected students in the university in an attempt to elicit the attitude and usage of the informants to Nigerian Pidgin English. The results were calculated in percentages. It was found that the attitude of Nigerian students regarding the Nigerian Pidgin English in UPM is positive. To conclude, in the next few years, Nigerians are expected to use Nigerian Pidgin English in all situations when they communicate.